2018
DOI: 10.5713/ajas.17.0545
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between blood, physiological and behavioral parameters in beef calves under heat stress

Abstract: ObjectiveThe performance, health, and behaviour of cattle can be strongly affected by climate. The objective of this study was to determine the effect of heat stress on blood parameters, blood proteins (haptoglobin [Hp]; heat shock protein 70 [HSP70]), rectal temperature (RT), heart rate (HR) and rumination time in Korean native beef calves.MethodsThirty-two Korean native beef calves were randomly assigned to 8 groups with 4 animals per group. They were kept in environmental condition with temperature-humidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 34 publications
7
63
0
2
Order By: Relevance
“…Liver disorder was further confirmed by liver function test with higher value of serum GPT and GOT in this study. Kim et al () also documented enzyme activity of similar nature due to thermal stress in beef calves. Value of lower serum protein, albumin and higher GOT, GPT were previously found for other higher organism under thermal stress (Hooda & Upadhyay, ).…”
Section: Discussionmentioning
confidence: 90%
“…Liver disorder was further confirmed by liver function test with higher value of serum GPT and GOT in this study. Kim et al () also documented enzyme activity of similar nature due to thermal stress in beef calves. Value of lower serum protein, albumin and higher GOT, GPT were previously found for other higher organism under thermal stress (Hooda & Upadhyay, ).…”
Section: Discussionmentioning
confidence: 90%
“…Cold stress causes negative effects on growth performance and immune cell population by influencing metabolic and immunological activities [5,6]. Thus, hematological profiles, if measured, could be a good indicator of how stressors affect the immune function of the body [6][7][8][9]. The thermo-neutral zone for growing Korean native beef cattle is approximately 4 to 20 • C, and the critical temperature is approximately −10 • C [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of significant variation in glucose behavior over time and in treatments was expected (HORNICK et al, 1998) since the blood glucose content has few variations in the ruminants due to the very efficient homeostatic mechanisms of the organism, except in animals with severe malnutrition (GONZÁLEZ and SCHEFFER, 2003) or subjected to intense heat (KIM et al, 2018), cases in which a decrease in blood glucose concentration may be observed (ELLENBERGER et al, 1989). In cases where the feed restriction has been imposed for long periods, the responses of the animals can be quite variable (NRC, 1996) as a function of the metabolic changes provided by the compensatory weight gain (BLUM et al, 1985;ELLENBERGER et al, 1989;HAYDEN et al, 1993).…”
Section: Discussionmentioning
confidence: 99%